2013
DOI: 10.1108/ijrdm-06-2012-0056
|View full text |Cite
|
Sign up to set email alerts
|

A typology of Indian hypermarket shoppers based on shopping motivation

Abstract: Purpose – Hypermarket is the most successful amongst organised retail formats in India. The purpose of this paper is to identify segments of hypermarket shoppers based on shopping motivation. The study profiles the identified segments on demographic characteristics and shopping outcomes, and compares the shopping motivation of hypermarket consumers with that of traditional store shoppers. Design/methodology/approach – The study involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…They uncovered some differences in cross-format patronage between their shopper types but primarily, they found that all four retail formats were patronised by all shoppers, suggesting that shopping motivation is not the main driver of retail format choice. However, their motivation measures related to shopping in general and not specifically to grocery shopping, whereas Mehta et al's (2014) study of Indian grocery shoppers found that motivations to shop at hypermarkets versus traditional stores differed. Nilsson et al (2015) also researched grocery store formats and examined Swedish grocery shoppers' use of supermarkets and convenience stores for major and for top-up shopping trips.…”
Section: In-store Grocery Shopper Typologiesmentioning
confidence: 90%
See 2 more Smart Citations
“…They uncovered some differences in cross-format patronage between their shopper types but primarily, they found that all four retail formats were patronised by all shoppers, suggesting that shopping motivation is not the main driver of retail format choice. However, their motivation measures related to shopping in general and not specifically to grocery shopping, whereas Mehta et al's (2014) study of Indian grocery shoppers found that motivations to shop at hypermarkets versus traditional stores differed. Nilsson et al (2015) also researched grocery store formats and examined Swedish grocery shoppers' use of supermarkets and convenience stores for major and for top-up shopping trips.…”
Section: In-store Grocery Shopper Typologiesmentioning
confidence: 90%
“…Bellenger and Korgaonkar, 1980;Westbrook and Black, 1985;Williams et al, 1985;Reid and Brown, 1996;Reynolds et al, 2002;Arnold and Reynolds, 2003; see also Mehta et al, 2014 for a review of shopper typology studies). As shopping evolved and retail store formats diversified, researchers have examined the continued applicability of these general shopper typologies and found that different (bricks and mortar) retail formats are patronised by mostly common shopper types (e.g.…”
Section: General Shopper Typologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Westbrook and Black, 1985) have been based specifically on one or the other, subsequent researchers have conflated them. There is no consensus among researchers as to the precise definitions of shopping orientation and shopping motivation (Wagner and Rudolph, 2010) and they are often used interchangeably (Bellenger and Korgaonkar, 1980;Chetthamrongchai and Davies, 2000;Mehta et al, 2014). Reviews of shopper typologies (e.g.…”
Section: Shopping Motivation and Shopping Orientationmentioning
confidence: 99%
“…[25,28,33]. Other studies focus on consumer expenditure [33][34][35] and number of visits [36][37][38]. Nilsson et al empirically analyzed how the socio-demographic characteristics and shopping behavior of Swedish consumers relate to shop attributes in order to understand the determining factor in shop selection [39].…”
Section: Literature Reviewmentioning
confidence: 99%